Current status of pig lung xenotransplantation. (November 2015) - Kubicki, Natalia; Laird, Christopher; Burdorf, Lars; Pierson, Richard N.; Azimzadeh, Agnes M.
Abstract: Human organ transplantation has improved duration and quality of life for many people, but its full potential is critically limited by short supply of available organs. One solution is xenotransplantation, although this comes with its own set of challenges. Lungs in particular are highly sensitive to injury, during the transplantation process generally, and to multiple immune rejection mechanisms. Using pig lung donors, our lab has been working on lung transplants into baboons as a surrogate for a human recipient. Several ex vivo human blood perfusion models have also proven useful. The combination of these experiments allows us to test large animal models as well as whole organ or isolated endothelial reactions to perfusion with human blood. We have found that a multi-modality therapeutic approach to prevent various pathogenic cascades – such as antibody-driven complement activation, other immune pathway activation, thrombosis, and tissue ischemia-reperfusion injury – has met with progressively greater success to protect the xeno lung from injury. Pig gene knockout and human gene transfer has been perhaps the greatest contributor. This review will discuss mechanisms of xeno lung injury, relevant experimental models, as well as recent results and future targets for research. Highlights: We review the current status of lung xenotransplantation. We provide an overview of the unique challenges associated with lung xenotransplantation. Clinical models used to study lung xenotransplantation are outlined. We summarize emerging means of overcoming lung xenograft injury.